1989
DOI: 10.1126/science.2928783
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Protein Enhances the Survival of Hippocampal Neurons in Vitro

Abstract: The beta-amyloid protein is progressively deposited in Alzheimer's disease as vascular amyloid and as the amyloid cores of neuritic plaques. Contrary to its metabolically inert appearance, this peptide may have biological activity. To evaluate this possibility, a peptide ligand homologous to the first 28 residues of the beta-amyloid protein (beta 1-28) was tested in cultures of hippocampal pyramidal neurons for neurotrophic or neurotoxic effects. The beta 1-28 appeared to have neurotrophic activity because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
173
0
2

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(191 citation statements)
references
References 25 publications
16
173
0
2
Order By: Relevance
“…Thus, the peptide did not cause general impairment of ability to recall stored information. Depending on conditions, A/3P has been found to exert both toxic and trophic effects on cells in culture (33)(34)(35). In the present experiments, four peptides homologous to A,8P were found to be amnestic in mice, a demonstration of effects on quantitatively measurable variables in an intact behaving organism.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the peptide did not cause general impairment of ability to recall stored information. Depending on conditions, A/3P has been found to exert both toxic and trophic effects on cells in culture (33)(34)(35). In the present experiments, four peptides homologous to A,8P were found to be amnestic in mice, a demonstration of effects on quantitatively measurable variables in an intact behaving organism.…”
Section: Resultsmentioning
confidence: 99%
“…Our study has focused on the possibility that neuritic retraction and/or neuronal dystrophy associated with Alzheimer-like plaques is not simply a consequence of ,B-AMYLOID INDUCES GLIOSIS 297 direct neurotoxicity by ,B-amyloid (as it has been suggested in solution (15,20,(34)(35)(36) or as insoluble peptide aggregates (8,24), but also of secondary glial cell reactions to the insoluble molecule. The ,B-amyloid peptides I were bound to a substrate in our experimental model systems and, therefore, it may be argued that this presentation of ,B-amyloid peptides to cortical cells more closely mimics the situation of AD plaques in vivo where p-amyloid is present in fibrillar form.…”
Section: Discussionmentioning
confidence: 99%
“…Glial cells traversed the border on and off the peptide sub- [25][26][27][28][29][30][31][32][33][34][35] peptide spots, cells remain resident for many days but gradually the density on these peptides declines at comparable rates (n = 46). Cells on the scrambled 1-40 and [25][26][27][28][29][30][31][32][33][34][35] peptide spots remain at similar densities as on the surrounding substrate (n = 12) .. strate freely, indicating that the border of the peptide was not a physical barrier to cell movements and that the peptides were not inherently nonadhesive or repulsive to glial cells. Glial cells do not exhibit increased motility or the same changes in morphology in preparations of scrambled 25-35 or scrambled 1-40 peptides.…”
Section: Behavior Of Cortical Glia On {3-amyloid Substratesmentioning
confidence: 99%
“…In vivo, small, stable oligomers of A␤-(1-42) have been isolated from brain, plasma, and cerebrospinal fluid (8 -10) and correlate with the severity of neurodegeneration in AD (11, 12). Thus, although genetic evidence predicts that A␤ is a causative factor in AD, the role of fibrillar and oligomeric A␤ in the pathogenesis of AD remains unclear.Initial in vitro studies suggested that A␤-induced neurotoxicity required the peptide to adopt a fibrillar aggregation state, with unaggregated peptide at low doses actually exhibiting neurotrophic effects (13)(14)(15)(16)(17)(18)). Recent studies demonstrate that non-fibrillar structures, including oligomers and amyloid-derived diffusible ligands (ADDLs) (19 -23), and protofibrils (24 -26) are also neurotoxic.…”
mentioning
confidence: 99%